KARAKTERISASI BAHAN FERROELEKTRIK BARIUM STRONTIUM TITANAT (Ba0.3 Sr 0.7TiO3) DENGAN MENGGUNAKAN DIFRAKSI SINAR-X (XRD) - Rahmad Efendi; Rahmi Dewi; Krisman ' (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
Ferroelectric materials of Barium Strontium Titanate (BST) with its composition of Ba0,3Sr0,7TiO3 was succesfully deposited by a solid solution method. The samples were prepared in the form of pellets and then were annealed at the temperature of 600, 700, 800oC. Characteritation of the samples was performed using X-Ray diffraction (XRD). The results of characteritation using XRD was described on a graph of the intensity vs. 2 theta. The XRD patterns of Ba0,3Sr0,7TiO3 have peaks. It was confirmed that the material of Ba0,3Sr0,7TiO3 has cubic crystalline structure, and its lattice parameter was in average of 3,961 Å. The particle sizes (D) and lattice strains (η) of the material that was annealed at temperature of 600, 700, 800°C for 1 hour were 42.60, 44.43, 46.89 nm and -4,49x 10-3, -4,05 x 10-3, -2,96 x 10-3, respectively. The increase in annealed temperature will raise the particle size and lattice strain.